Risk Factor Analysis which Affect Severity of Low Back Pain to ward The Patients of Medic Rehabilitasion Intsalasi in RSUP dr. Mohammad Hoesin Palembang in 2016-2017. - Emirzon, M Afif Baskara; Hadani, M Hasnawi; Larasati, Veny (Sriwijaya Journal of Medicine, 2018)
The incidence of lower back pain in the productive age population continues to increase. Various risk factors such as age, sex, smoking, and physical activity, length of work and work position can exacerbate lower back pain complaints. This study was conducted to analyze risk factors that affect the severity of low back pain in patients who perform therapy in Medical Rehabilitation Installation RSUP dr. Mohammad Hoesin Palembang period 2016-2017. The research used is analytical observation with cross-sectional technique. The sample of research is 71 respondents in Medical Rehabilitation Installation of dr. Mohammad Hoesin Palembang that meets the inclusion criteria. The data was further processed and grouped in table form. At 71 respondents found 49 respondents suffered severe NPB and 22 respondents suffered from mild NPB. The results showed that sex, physical activity, work position and duration of work had significant relationship with mild cases of low back pain (p = 0,03, p = 0,000, p = 0,00, p = 0,002). While age, smoking, BMI did not have a significant association with mild cases of low back pain (p = 0.08, p = 1.044, p = 0.690). Risk factors that affect the severity of lower back pain are male, physical weight, working position sitting or bending and length of work more than 7 hours per day.